Minimally Invasive Plate Osteosynthesis with Locking Compression Plate for Distal Diametaphyseal Tibia Fracture - Shrestha, D; Acharya, B M; Shrestha, P M (Kathmandu University Medical Journal, 2012)
Background Distal diametaphyseal tibia fracture though requires operative treatment is difficult to manage. Conventional osteosynthesis is not suitable because distal tibia is subcutaneous bone with poor vascularity. Closed reduction and minimally invasive plate osteosynthesis (MIPO) with locking compression plate (LCP) has emerged as an alternative treatment option because it respects biology of distal tibia and fracture hematoma and also provides biomechanicaly stable construct. Objectives To find out suitability of MIPO with LCP for distal diametaphyseal tibia fracture including union time and complicatios and compare wih other available management options in literature. Methods Twenty patients with closed distal diametaphyseal tibia fracture with or without intra articular extension (AO classification: 12 type 43A1, 4 type 43A2, 2 type 43A3 and 2 type 43B1) treated with MIPO with LCP were prospectively followed for average duration of 18.45 months (range 5-30 months). Results Average duration of injury-hospital and injury-surgery interval was 12.8 hrs (range 2-44 hrs) and 4.45 days (range 1-10 days) respectively. All fractures got united with an average duration of 18.5 weeks (range14-28weeks) except one case of delayed union which was managed with percutaneous bone marrow injection. Two patients had union with valgus angulation < 5 degees but no nonunion was found. There were two superficial and one deep post operative wound infection. All infections healed with extended period of intravenous antibiotics besides repeated debridemet for deep infection. Implants were removed in eight patients among whom six (30%) had malleolar skin irritation and pain due to prominent hardware. Conclusion The present case series shows that MIPO with LCP is an effective treatment method in terms of union time and complications rate for distal diametaphyseal tibia fracture. Malleolar skin irritation is common problem because of prominent hardware. DOI: http://dx.doi.org/10.3126/kumj.v9i2.6291 Kathmandu Univ Med J 2011;9(2):62-8